Book Review: RECLAIMING BUKOVINA’S MUSICAL FOLKLORE HERITAGE COLLECTED BY ALEXANDRU VOEVIDCA AT THE BEGINNING OF THE 20TH CENTURY FOR THE CONTEMPORARY: Alexandru Voevidca, "Folclor muzical din Bucovina – vol. I – Repertoriul ritual-ceremonial vocal", ediţie critică şi catalog tipologic muzical de Dr. Constanţa Cristescu, Suceava: Editura Lidana, 2015 / Alexandru Voevidca, "Musical Folklore from Bukovina – vol. 1 – Vocal repertoire for Rituals and Ceremonials", Suceava: Lidana Publishing House, 2015. - DĂNILĂ, Irina Zamfira (Studia Universitatis Babes-Bolyai Musica, 2017)
The general issue of reclaiming and preserving the musical folklore heritage is crucial within the framework of our postmodern world; at present, due to the major changes in society following technological advances and globalization, folklore has undergone important mutations. It therefore requires a considerable effort to research and document national or local archives; the results of this efforts are usually remarkable. Is is the case of the latest achievement by Constanţa Cristescu, PhD, from the Bukovina Culture Centre of Suceava, a distinguished musicologist and an impassionate, tireless and prolific researcher; in the past years, she has been active in supporting, investigating and promoting genuine folklore from Bukovina. The volume with the title Musical Folklore from Bukovina – vol. 1 – Ritual vocal repertoire for rituals and ceremonies is the first one in a larger project aimed at introducing to the public the volumes of folklore collected by Alexandru Voievidca at the beginning of the 20th century in Austro-Hungarian Bukovina, a project the researcher intends to complete in the coming years.